Chemical composition of Agarwood Essential Oil (Aquilaria malaccensis) upon exposure towards heat condition - Hezelin Elayana, Shaian; Che Mohd Aizal, Che Mohd; Saiful Nizam, Tajuddin (Malaysian Institute of Chemistry, 2021)
Agarwood (Gaharu) is highly valued due to extensive usage in industries including perfumery, pharmaceutical and traditional medicine. The strong and unique woody aroma of agarwood oil is dependent on the abundance of sesquiterpenoid or oxygenated sesquiterpene. Post-treatment of agarwood oil such as exposure towards heat, UV light and oxygen under certain period of time are practiced by the industry to induce the formation of sesquiterpenoid content through the oxidation process, thus enhancing the woody aroma of the oil. In this study, agarwood oil (Aquilaria malaccensis) from Pahang, Malaysia was subjected to exposure of heat at 40 oC for periods of 3, 7, 14, 20 and 30 days. Gas chromatography analysis identified the major compounds in the oils as 9-hydroxyselina- 4,11-dien-14-oic acid (6.94-8.06 %), epi-α-cadinol (6.38-7.88 %), selina-3,11-dien-9-al (5.20-6.72 %), β-eudesmol (3.95-5.22 %), 10-epi-γ-eudesmol (3.95-3.87 %), selina-4,11- dien-14-oic acid (4.21-4.85 %), and α-eudesmol (3.25-3.79 %), kusunol (1.77-3.02 %) and kessane (2.42-2.90 %). The classification of compounds of treated oil (Day 3 to Day 30) showed that the sesquiterpenoid group dominated the aromatic compounds of agarwood oil in the range of 62.82 to 66.25 % with the highest content on Day 14. However, further investigation showed a decrease in total sesquiterpenoid content from 70.85 % (Day 0 to 66.25 % (Day 14) suggesting that the heating process did not increase the quantity of sesquiterpenoids as intended. Thus, further study with other parameters such as oxygen and UV light is recommended to be done together with headspace analysis of the samples.